2023
DOI: 10.1017/rdc.2023.30
|View full text |Cite
|
Sign up to set email alerts
|

The Swan Point Site, Alaska: The Chronology of a Multi-Component Archaeological Site in Eastern Beringia

Abstract: The Swan Point site in interior Alaska contains a significant multi-component archaeological record dating back to 14,200 cal BP. The site’s radiocarbon (14C) chronology has been presented in scattered publications that mostly focus on specific archaeological periods in Alaska, in particular its terminal Pleistocene components associated with the East Beringian tradition. This paper synthesizes the site’s 14C data and provides sequential Bayesian models for its cultural zones and subzones. The 14C and archaeol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Because ribs may bear heavy traces of damage through carnivore feeding on carcasses, including those of elephants, these ribs may also indicate early access to the ribs before carnivore feeding ( 52 ), further suggesting a hunting scenario. Redating of the Swan Point mammoth tusk ( 33 ) showed that she was contemporary with the earliest human occupation of Swan Point, CZ4b. She was also around 20 years old at the time of death, which is in the prime of early adulthood, with no evidence of nutritional stress in the δ 15 N values (Supplementary Text).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because ribs may bear heavy traces of damage through carnivore feeding on carcasses, including those of elephants, these ribs may also indicate early access to the ribs before carnivore feeding ( 52 ), further suggesting a hunting scenario. Redating of the Swan Point mammoth tusk ( 33 ) showed that she was contemporary with the earliest human occupation of Swan Point, CZ4b. She was also around 20 years old at the time of death, which is in the prime of early adulthood, with no evidence of nutritional stress in the δ 15 N values (Supplementary Text).…”
Section: Discussionmentioning
confidence: 99%
“…The Swan Point adult mammoth tusk was previously interpreted as having been scavenged in a subfossilized state based on its slightly older age relative to other dated samples from the cultural occupation ( 25 ). However, a new radiocarbon date for this tusk produced a younger calibrated date between 13,810 and 14,068 ya ( 33 ), which overlaps with multiple hearth features, artifacts, and other mammoth remains in the same cultural zone (CZ4b) and indicates they were contemporaneous.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The Pleistocene sites of Alaska are mostly located in the Tanana and Nenana Valleys in central Alaska (Bever 2006;Blong 2018;Holmes 2001;Potter et al 2013; Figure 2). The site of Swan Point in the Tanana Valley yields the earliest known occupation of Alaska, being dated to circa 14,000 cal BP by 15 consistent AMS radiocarbon dates (Hirasawa and Holmes 2017;Holmes 2011;Lanoë and Holmes 2016;Potter et al 2013;Reuther et al 2023;Supplemental Table 1). It is currently the only known site in northern North America where the Yubetsu method is exclusively used to systematically produce microblades (Gómez Coutouly and Holmes 2018).…”
Section: Swan Point and The Peopling Of Eastern Beringiamentioning
confidence: 99%